THE FRENCH APPROACH TO COMBATING THE ILLICIT TRAFFICKINGOF NARCOTIC DRUGS - Musaev Djamaliddin Kamalovich (American Journals Publishing, 2025)
The article analyzes the positive experience of France in developing unified approaches to combating crime in the field of illicit drug trafficking. The main achievements of the practical implementation of French state policy in the field of combating drug crime are considered. The basic directions of the national strategy to combat drug addiction in France are outlined. Features of international cooperation in the fight against drug crime. The scientific novelty of the study is determined by a systematic analysis of the features of the French national strategy in the field of combating drug trafficking. The information obtained as a result of the study is also novel, and is of interest for the further development of scientific research and improvement of the fight against drug addiction.